The Fusion Activity of IM30 Rings Involves Controlled Unmasking of the Fusogenic Core - Thurotte, Adrien; Schneider, Dirk (Frontiers in Plant Science, 2019)
The inner membrane-associated protein of 30 kDa (IM30, also known as Vipp1) is required for thylakoid membrane biogenesis and maintenance in cyanobacteria and chloroplasts. The protein forms large rings of ~2 MDa and triggers membrane fusion in presence of Mg2+. Based on the here presented observations, IM30 rings are built from dimers of dimers, and formation of these tetrameric building blocks is driven by interactions of the central coiled-coil, formed by helices 2 and 3, and stabilized via additional interactions mainly involving helix 1. Furthermore, helix 1 as well as C-terminal regions of IM30 together negatively regulate ring-ring contacts. We propose that IM30 rings represent the inactive form of IM30, and upon binding to negatively charged membrane surfaces, the here identified fusogenic core of IM30 rings eventually interacts with the lipid bilayer, resulting in membrane destabilization and membrane fusion. Unmasking of the IM30 fusogenic core likely is controlled by Mg2+, which triggers rearrangement of the IM30 ring structure.